Capacidad antiangiogénica comparada de celecoxib y anticuerpos neutralizantes anti-VEGF en un modelo in vivo - Vargas O., Julio; Vera N., Sergio; Zerega R., Andrés; Sinning O., Mariana; Fuenzalida B., Marcela; Rosas C., Carlos (Revista Hospital Clínico Universidad de Chile, 2014)
Introduction: A common feature in cancer is the development of angiogenesis, defined as the formation of blood vessels from preexisting ones, highly developed in malignant neoplasms to establish the prevalence of angiogenic factors over anti-angiogenic factors, which in physiological conditions are balanced. While there are currently several antiangiogenic therapies, the compared effect of celecoxib and anti-VEGF antibodies has not been performed on an in vivo model, such as chick chorioallantoid membrane (CAM). Materials and Methods: In this investigation, Methotrexate-resistant TA3 tumor supernatant (TA3-MTX-R) was instilled on the CAM, where a group was also treated with anti-VEGF165 antibodies (20 μg/mL) and another was treated with celecoxib in a concentration of 1000 ppm. Samples were processed histologically and stained with Hematoxylin Eosin-Alcian Blue. Double blind in blood vessels counting was performed using an optical microscope at 400x. Results: Both treatments promote reduced vascular density, where group treated with anti-VEGF antibodies was more antiangiogenic than group treated with celecoxib (p < 0.05). Conclusions: anti-angiogenic anti-VEGF potential and its greater efficacy compared with celecoxib is evident, due to their different mechanisms of action. Future studies should involve the co-adjuvant effect between celecoxib and anti-VEGF in cancer patients resistant to treatment with methotrexate.